A new integrable nonlocal modified KdV equation: Abundant solutions with distinct physical structures - Abdul-Majid Wazwaz (Journal of Ocean Engineering and Science, 2017)
In this work we study a new integrable nonlocal modified Korteweg–de Vries equation (mKdV) which arises from a reduction of the AKNS scattering problem. We use a variety of distinct techniques to determine abundant solutions with distinct physical structures. We show that this nonlocal equation possesses a family of traveling solitary wave solutions that include solitons, kinks, periodic and singular solutions.